The Formulation and Analysis of Solid Bath Soap from Ethanol Extract Of Kaffir Lime Peel (Citrus hystrix DC.) With Several Concentrations - latirah latirah; Priyanto Dwi Nugroho; Dodi Irwandi (Politeknik Kesehatan Kemenkes Jakarta II, 2022)
Solid bath soap is a cosmetic preparation to remove dirt from skin surfaces. Kaffir lime peel is a good natural ingredient for skin health. The aim of this study was to produce cosmetic preparation of solid bath soap from a thick extract kaffir lime peel with several concentrations. The thick extract of kaffir lime peel is made by maceration by dissolving 500 grams of powder with 96 % ethanol as solvent as much as 1,000 mL for 2x24 hours and concentrated using a rotary evaporator at 500 C. the method used in soap making is cold processing. The result of the study was a solid bath soap, smelling of fresh orange, bluish color to turquoise blue depends on the concentration of the active substance of kaffir lime extract, soft texture and homogeneous color, Formula 1 with concentration of kaffir lime peel extract of 1 % has pH 10.0, foam height of 5.0 cm, water content was 1.76% and free fatty acids was 2.51%. Formula 2 with concentration was kaffir lime peel extract of 3 % value pH 10.0, foam height of 5.0 Cm, moisture content of 1.95 % and free fatty acids was 2.51 % while formula 3 with an extract of 5 % has a pH 10.0 foam height was 5.0 cm, water content was 0.73 % and free fatty acid was 2.51 %. Solid bath soap with thick extract off kaffir lime peel meets the requirements of SNI number 3532 of 2016 for pH, and moisture content tests while the free fatty acid test does not meet these requirements of SNI